Signifikansi Penggunaan Augmented Reality dengan Geogebra dalam Memahami Materi Interval pada Mahasiswa Pendidikan Matematika UNIMED - Cristin Gultom; Angel Ramayanti Samosir; Nova Marcelina Sitanggang; Sisilia Nababan; Michael Christian Simanullang (EduInovasi: Journal of Basic Educational Studies, 2025)
Understanding the concept of intervals in mathematics is a fundamental aspect that is often a challenge for students. Augmented Reality (AR) with GeoGebra offers an interactive approach that can improve understanding of abstract concepts such as intervals. This research aims to analyze the effect of using Augmented Reality with Geogebra on students in understanding interval material. This research uses a qualitative descriptive method with the research subjects being students of the Mathematics Education Study Program, Medan State University. Data was collected through a written test in the form of essay questions. The research results show that Augmented Reality helps students with a visual learning style understand interval material. Students' difficulties in understanding interval material are quite varied. The causes of these errors include a lack of understanding of the concept and a lack of practice questions. It is hoped that this research can contribute to increasing students' understanding of interval material using the help of Argmented Reality with GeoGebra.